“Do We Think Alike?” – Experts’ Views on the Aesthetic Perception of Pua Kumbu Design Motifs’ Visual Complexity - Wan Juliana Emeih Wahed; Noorhayati Saad; Saiful Bahri Mohd Yusoff (Journal of Visual Art and Design, 2023)
Aesthetic perceptions are influenced by the formal aspects and visual substance of art, which prompt individuals to respond and reconsider their perspective. The purpose of this study was to evaluate experts’ aesthetic perceptions of the complexity of Pua Kumbu design motifs. The complexity of the symbols found in the design motifs contributes to a lack of interest in understanding the meanings of these motifs, particularly among the younger generation. Therefore, through the utilization of interviews with structured and unstructured questions, a qualitative technique was employed to investigate the experts’ aesthetic perception of the visual complexity of the design motifs. The findings provide a fundamental understanding and emphasize the importance of preserving traditional human values, with the hope that hand weaving, as a valuable heritage, will endure and maintain its significance in the long term.